2009
DOI: 10.1063/1.3063655
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on resonance Raman and hyper-Raman scatterings for a centrosymmetric distyrylbenzene and relationship to two-photon absorption

Abstract: Resonance Raman (RR) and resonance hyper-Raman (RHR) spectra have been obtained for a nominally centrosymmetric dialkylammonium-substituted distyrylbenzene that was previously shown to exhibit a strong solvent polarity effect on its two-photon absorption strength. Spectra have been obtained in acetonitrile, methanol, dimethylsulfoxide, and water. In each solvent, the RR and RHR spectra show very similar intensity patterns in the strongest lines in both the C=C and C-C stretching regions, but the RHR peaks are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Nguyen et al recently calculated 2PA cross sections and spectra of ED- or EW-substituted Pt acetylide complexes with structures related to the series studies here and showed that low barriers for rotations of the alkylphosphinyl and phenylene groups may lead to multiple low-lying conformers with different (lower) symmetries; however, no substantial effects of the conformational changes on the 2PA properties were predicted . Leng et al used hyper-Raman and hyper-Rayleigh scattering to show that in some nominally centrosymmetric metal-free chromophores the inversion symmetry could be broken in vertical transitions by interactions with solvent, even though the 2PA spectra indicated mostly quadrupolar behavior …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nguyen et al recently calculated 2PA cross sections and spectra of ED- or EW-substituted Pt acetylide complexes with structures related to the series studies here and showed that low barriers for rotations of the alkylphosphinyl and phenylene groups may lead to multiple low-lying conformers with different (lower) symmetries; however, no substantial effects of the conformational changes on the 2PA properties were predicted . Leng et al used hyper-Raman and hyper-Rayleigh scattering to show that in some nominally centrosymmetric metal-free chromophores the inversion symmetry could be broken in vertical transitions by interactions with solvent, even though the 2PA spectra indicated mostly quadrupolar behavior …”
Section: Introductionmentioning
confidence: 94%
“…22 Leng et al used hyper-Raman and hyper-Rayleigh scattering to show that in some nominally centrosymmetric metalfree chromophores the inversion symmetry could be broken in vertical transitions by interactions with solvent, even though the 2PA spectra indicated mostly quadrupolar behavior. 37 Here we use femtosecond 2PEF and NLT measurements in the S 0 → S 1 transition region to show that the effective symmetry of the Pt complexes strongly depends on the substitutions, where only ED or neutral substituents exhibit the 2PA spectra consistent with centrosymmetric or nearly centrosymmetric structure, whereas strong EW substituents lead to a complete breaking of the inversion symmetry. The resulting dipolar behavior of the EW-substituted complexes is clearly manifested in the appearance of the S 0 → S 1 transition in the 2PA spectrum, large peak 2PA cross section values up to σ 2 ∼ 700 GM, and large permanent electric dipole moment changes up to ∼10−20 D, all corresponding to this transition.…”
Section: Introductionmentioning
confidence: 99%
“…3 We have previously demonstrated this in conjugated organic molecules; resonance hyper-Raman scattering is strong in highly asymmetric, donor-acceptor substituted "push-pull" molecules, while in symmetrically substituted, nominally centrosymmetric systems the hyper-Raman scattering is observable but very weak, presumably allowed through ground-state conformational distortions and/or transiently asymmetric solvation. [4][5][6] Here we extend these studies to II-VI semiconductor nanocrystals. There have been some prior studies of both electronically nonresonant [7][8][9][10][11] and resonant [12][13][14][15] hyper-Rayleigh scattering in II-VI quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 72%
“…Hyper-Raman scattering in such systems is allowed only through vibronic coupling mechanisms and is generally expected to be weak . We have previously demonstrated this in conjugated organic molecules; resonance hyper-Raman scattering is strong in highly asymmetric, donor–acceptor substituted “push–pull” molecules, while in symmetrically substituted, nominally centrosymmetric systems the hyper-Raman scattering is observable but very weak, presumably allowed through ground-state conformational distortions and/or transiently asymmetric solvation. …”
Section: Introductionmentioning
confidence: 94%
“…Only a few studies of the TPA properties , have been carried out, in which solvent effects are discussed. Usually, solvent effects are identified in correlations between the molecular property in question and the dielectric constant of the solvents or various reaction field parameters.…”
Section: Resultsmentioning
confidence: 99%